1989
DOI: 10.1002/jso.2930400303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histopathological appraisal of preoperative irradiation for adenocarcinoma of the pancreatoduodenal region

Abstract: A retrospective review to elucidate the rationale of preoperative irradiation was made on 18 carcinomas of the head of the pancreas area. After 50 Gy/25 fractions of 10 MV X-ray was given, all 18 tumors decreased from 3.3 +/- 0.8 cm to 2.0 +/- 0.7 cm. At the surgical operation, 16 patients (89%) received pancreatic resection, without operative death. Histologically, in 13 of these 16 cases, the population of severely degenerative cancer cells (SDCC) was more than 1/3 of all cancer cells, and SDCCs were likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 11 publications
3
46
0
1
Order By: Relevance
“…Although neoadjuvant therapy may allow resection in patients with an initially unresectable disease, the high incidence of recurrence, as in the present case, emphasizes the systemic behavior of the disease. This raises the question if palliative systemic chemotherapy and/or chemoradiation may achieve the same outcome, avoiding the morbidity and potential mortality of surgery (66). In the future, biomarkers may assist clinicians in decisional processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neoadjuvant therapy may allow resection in patients with an initially unresectable disease, the high incidence of recurrence, as in the present case, emphasizes the systemic behavior of the disease. This raises the question if palliative systemic chemotherapy and/or chemoradiation may achieve the same outcome, avoiding the morbidity and potential mortality of surgery (66). In the future, biomarkers may assist clinicians in decisional processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several variables of tumor response to neoadjuvant therapy have been proposed, including the number of severe degenerative cancer cells (SDCC), percentage of viable cells, degree of fibrosis or presence of necrosis (69,70). In a trial using SDCC to evaluate response to preoperative therapy, no advantage in terms of OS was observed in 13/26 patients who achieved a major response, defined as >80% SDCC (66). In trials where the percentage of remaining viable cells was evaluated, the patients whose tumors demonstrated minimal pathologic response exhibited more than twice the risk of mortality compared with patients who achieved a partial response or pCR (HR=2.74; P=0.01); although significant, this finding should be interpreted with caution, due to the small sample size (37,39).…”
Section: Discussionmentioning
confidence: 99%
“…CRT associated with PD enabled the optimal local control of the disease, as confirmed by tumor downstaging (one patient with ypT0 stage tumor and 2 patients with minimal residual disease), margin free resections and no identified local recurrences [25][26][27][28] . However, outstanding local control did not prevent distant recurrences and 4 resected patients experienced metastatic spread.…”
Section: Future Strategiesmentioning
confidence: 86%
“…This may eventually translate into a better therapeutic index [11]. There are three main reasons favoring the idea of preoperative chemoradiation: (1) a higher rate of complete resections could be achieved by tumor downstaging; (2) in the preoperative setting, perfusion and oxygenation of peritumoral and tumoral tissue are enhanced and thus a higher efficacy of RT can be expected according to radiobiological principles [12]; (3) the dorsal resection margin is critical in Whipple's procedure, often leaving only a minimal margin of nontumorous tissue in the retroperitoneal direction. Complete resection often fails in this region [13].…”
Section: Introductionmentioning
confidence: 99%
“…The first trials with preoperative radiation (RT) of pancreatic carcinoma [1,2] showed longer survival for the subgroup of resected patients undergoing surgery after irradiation compared with nonresectable patients and stimulated further studies of preoperative chemoradiation (CRT) [3][4][5][6][7][8][9][10]. Today, marked improvements in CT and MRI allow better assessment of resectability and are essential for the decision whether a patient should be included into or excluded from neoadjuvant protocols.…”
Section: Introductionmentioning
confidence: 99%